Potential of Surface Functionalized Nanomaterials in Innovative Drug Development: A Mini-review - Ditta, Sarwar A.; Yaqub, Atif; Tanvir, Fouzia (Letters in Drug Design & Discovery, 2024)
The unique properties of nanomaterials (NMs) make them special entities for biomedical innovation and research. Early diagnosis and follow-up of diseases are easily possible with the help of nanotechnology and nanomedicine, which can help combat any medical condition. Surface functionalization with specific molecules might impart marked properties to NMs, leading to the modification of cellspecific interactions within the biological systems. This modification may provide excellent phenomena for innovative drug development. Modified NMs might play essential roles in various applications, i.e., in vivo diagnostics, magnetic resonance imaging (MRI), positron emission tomography (PET), etc. Functionalization of NMs with appropriate ligands, small molecules, or polymers assigned them enhanced stability, biocompatibility, and functionality for their novel and improved biological applications. Surface functionalized NMs might display enhanced antimicrobial, antidiabetic, and drug delivery potential for various applications. Different studies reported the potential of functionalized metallic nanoparticles in regenerative medicines. Conjugation of NMs with various molecules such as peptides, small ligands, polysaccharides, proteins, saturated and polyunsaturated fatty acids, siRNA, plasmids, and DNA, might be achieved by various reactions. Biomolecule-conjugated nanoparticles result in the production of hybrid NMs with specific and novel biological interactions in biological systems. Chemical treatment methods are considered among the most trusted and efficient functionalization methods. Some commonly used techniques and strategies of functionalization involve grafting to and grafting from methods, ligand exchange technique, covalent bonding, chemisorption, non-covalent interactions, electrostatic adsorption, etc. This brief review is dedicated to the surface functionalization of NMs with the latest development.
Keywords: grafting polymers